Recent Advances in Silicon Nanomaterial-Based Fluorescent Sensors - Wang, Houyu (Sensors (Basel), 2017)
During the past decades, owing to silicon nanomaterials’ unique optical properties, benign biocompatibility, and abundant surface chemistry, different dimensional silicon nanostructures have been widely employed for rationally designing and fabricating high-performance fluorescent sensors for the detection of various chemical and biological species. Among of these, zero-dimensional silicon nanoparticles (SiNPs) and one-dimensional silicon nanowires (SiNWs) are of particular interest. Herein, we focus on reviewing recent advances in silicon nanomaterials-based fluorescent sensors from a broad perspective and discuss possible future directions. Firstly, we introduce the latest achievement of zero-dimensional SiNP-based fluorescent sensors. Next, we present recent advances of one-dimensional SiNW-based fluorescent sensors. Finally, we discuss the major challenges and prospects for the development of silicon-based fluorescent sensors.